The Role of Gut Microbiota in Human Health: Implications for ‎Disease Prevention - Upadhyay, Dr. Satish; Maharana , Dr. Laxmidhar; Priscilla , G. Nancy; Gupta , Anchal; Joshi , Monika; Prasad , H. D. Raghavendra; Bhushan , Bharat (International Journal of Basic and Applied Sciences, 2025)
The host's metabolic health depends on the gut, which is home to trillions of microorganisms, because a healthy gut commensal microbiota ‎is linked to vital processes like digestion, xenobiotic degradation, energy harvesting from food components, water-soluble vitamin ‎production, and metabolite production. It has also been shown that these vital processes can support and improve the intestinal barrier's ‎integrity, the gut epithelium's functional ability, and the body's defense against harmful organisms. Dysbiosis, a disturbance in the ‎equilibrium of the host microbiota brought on by antibiotic usage, menopause, toxins, stress, and gut inflammation, is the cause of disorders ‎like heart disease, autoimmune diseases, autism, obesity, and type 2 diabetes. The expression of the junction protein was down-regulated as a ‎result of changes in intestinal microbial members and food patterns, which raised gut permeability at the epithelial layers. However, while ‎metformin tackles important metabolic abnormalities in type 2 diabetes, recent evidence underscores the necessity of treating the gut ‎microbiota to enhance glucose homeostasis. Bile acid (BA) metabolism, which is essential for controlling glucose, is one of the many ‎aspects of host metabolism that are significantly impacted by the gut microbiota‎.
Keywords: Gut Microbiota; Diseases; Prevention